Implementasi Pemungutan Pajak Bumi Dan Bangunan Perdesaan Dan Perkotaan (Pbb-P2) Dalam Peningkatan Pendapatan Asli Daerah (Pad) Di Kabupaten Barito Kuala - Wulan Wurnongo; Avela Dewi; Erma Ariyani (Jurnal Administrasi Publik dan Pembanguan, 2019)
Regional tax is one of the main in state revenues. With the existence of regional autonomy, members of the government are strong for autonomous regions, namely being able to organize and manage their own households. Local governments need to maximize the potential of local taxes. This research use qualitative method with qualitative descriptive type. Indicator Based From Tax implementation such as SISMIOP Maintenance data base, Mass print simulation, bulk print, Submission of SPPT and DHKP PBB, billing, payment and evaluation meeting, So the Results at BP2RD departure point can be concluded Good Enough Against Admissions PAD. Supported by the local government, sufficient budget and facilities. And the State Civil Apparatus, lack of socialization and public awareness as an inhibiting factor. This research recommends the BP2RD office of Barito Kuala District to be more active in registering and socializing the Land and Building Tax to the public so that the public is aware of paying land and building taxes.